Polymeric Switch on Lysozyme Activity: Role of Hydrophobic and Electrostatic Interactions - Dr. Sumon Ganguli; Md. Bellal Hossain (Chemistry Department, The University of Brawijaya, 2013)
Enzymes have attracted potential applications in both medicine and biotechnology. In our present study, we show a strategy for switching the enzymatic activity of lysozyme by the complex formation with a cationic smart copolymer. PAMA-g-PEG graft copolymers suppressed the enzymatic activity of lysozyme without any conformational change, indicating the formation of complex and covering the active site of lysozyme by copolymers. The addition of polyanion, poly(acrylic acid) (PAAc), recovered the suppressed enzymatic activity of the lysozyme/polymer complex efficiently. These finding suggest that that hydrophobic interaction coupled with electrostatic interactions has a great role for the complexation and decomplexation of the lysozyme/polymer complex. Circular dichroism (CD) spectral analysis indicated that the conformation of the enzymes maintained largely during the course of the complexation.